Immunogenicity Evaluation of Epitope-Based Vaccine on Target of RNAIII-Activating Protein (TRAP) of Staphylococcus Aureus - Simiao Yu; Di Yao; Xintong Wang; Wei Yu; Yuhua Wei; Wei Liu; Liquan Yu; Jinzhu Ma; Chunyu Tong; Jing Chen; Yongzhong Yu; Baifen Song; et al. (Biology, 2025)
Staphylococcus aureus is a leading cause of severe infections in humans and animals, and the emergence of multidrug-resistant strains highlights the need to develop effective vaccines to prevent such diseases. Epitope-based vaccines use short antigen-derived peptides corresponding to immune epitopes, which are administered to trigger protective humoral and cellular immune responses. In this study, in silico MHC affinity measurement methods were used to predict possible binding regions, and five 20-mer synthetic TRAP peptides (TRAPP) were synthesized. Epitope-based vaccines, named PT and PTR, incorporating the identified CD4+ T and B cell epitopes, were constructed. Peptides TRAP20–39 and TRAP94–113 elicited significant peptide-stimulated T-cell proliferation responses in vivo. Additionally, high levels of IFN-γ and IL-17A, along with moderate levels of IL-4, were detected in ex vivo stimulated CD4+ T cells isolated from rTRAP- and TRAPP-immunized mice, suggesting that these peptides are classified as Th1 and Th17 epitopes. Immunization with PT or PTR induces robust humoral and cellular immune responses. Moreover, the epitope-based vaccine, PT, exhibited a stronger protective immune response than the intact TRAP in a murine systemic S. aureus infection model. Based on the results presented herein, an epitope-based vaccine is a promising and potentially more effective candidate.